Basic properties of the problem of the best simultaneous approximation of several elements - Hnatyuk, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
For the problem of the best approximation of several elements with respect to the maximum of convex-concave fractional functions with additional restrictions, we establish duality relations and criteria for the element of the best approximation.